ISTIDLAL FATWA DEWAN SYARIAH NASIONAL TENTANG JUAL BELI EMAS TIDAK TUNAI - Zamani, Ahmad Zaki (Al-Banjari : Jurnal Ilmiah Ilmu-Ilmu Keislaman, 2016)
Fatwa of DSN-MUI No.77 / DSN-MUI / V / 2010 issued on June 3, 2010 states that selling and buying gold with non-cash payment is allowed (mubah) as long as the gold is not as the official medium of exchange (subtituting money) either through purchase or ordinary selling murabaha.This fatwa is controversial among scholars. Some argue that this fatwa is in contrast to the hadiths explaining that it is not allowed to sell an usury item with other item unless it is cash. It also should not be selled by loan although the items are in different types and sizes. The authors are interested in doing research with a focus on two issues, namely: the method of istinbath in a fatwa of DSN law on non-cash trade in gold and its relation with National Sharia Board Fatwa No.77 / DSN-MUI / V / 2010 On Selling and Buying Gold Non-Cash with four Imam sect.